A admissibilidade das provas ilícitas no processo penal - Paiva, André Luís Queiroz de (2016)
This monographic work's main object are the exclusionary rules of evidence in Brazilian law, especially in Constitution and in the criminal procedure law. The goal is to analyse the legal discipline of this theme under the neoconstitucional point of view, which is based on a broader scientific perspective characterized by the search for proportionality between the founding values and principles of the legal order and by the ultimate supremacy of human individual dignity. To achieve this task, this work will examine the juridical concept of evidence in general and specially in the criminal field, including in its historical evolution across the last centuries, and its discipline in Brazilian law. Thus, it will be demonstrated that the judicial refusal of illegally collected evidence does not offend, but it rather fulfills the social ends of jurisdiction and that, in the other hand, the exceptions admitted to this refusal in jurisprudence do not contradict its nature of constitutional guarantee. The method employed was bibliographical and legislative research.